Parameter design method for capacitive power and signal transfer system based on multi-objective optimisation algorithm - Su, Yu-Gang; Zhou, Wei; Wang, Zhi-Hui; Wu, Xue-Ying; Qing, Xiao-Dong (IET power electronics, 2019)
For most capacitive power transfer applications, a reliable signal transfer link between the primary side and the secondary side plays an essential role. The parameters design of the system has a key effect on the operating performance, however, the existing parameter design method can only get an acceptable solution, instead of a globally optimal solution. This study has proposed a general and global optimal parameter design method based on the constraint multi-objective algorithm. The mathematical models of the power and signal channels as long as the power noise is established and all the objective functions are given according to the models. Besides, the constraints considering the reasonable region of the parameter values and the limitation of the voltage and current on the elements are given. Then the multi-objective optimisation problem with the objective functions and constraints are solved by the non-dominated sorting genetic algorithm II, and the proper global optimal parameters are selected from the Pareto set. Finally, a simulation model and an experimental setup with 180 W power and 200 kbps signal transfer capability are constructed, and the results verified the effectiveness and correctness of this method.